Answer:
7
Step-by-step explanation:
Hey there!
In order to answer this question you need to substitute the "y-value"
As you can see, y=8 and we need to put 8 where there is y
8-3+2 is what the equation will look like
Now we can simplify
8-3 is 5 and 5+2 is 7
So your answer is 7
Answer:
D. ![= \frac{b}{a}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7Bb%7D%7Ba%7D%20)
Step-by-step explanation:
Given:
![\frac{b^{-2}}{ab^{-3}}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bb%5E%7B-2%7D%7D%7Bab%5E%7B-3%7D%7D%20)
Required:
Assuming a ≠ 0, b ≠ 0, find the expression equivalent to the given expression.
SOLUTION:
![\frac{b^{-2}}{ab^{-3}}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bb%5E%7B-2%7D%7D%7Bab%5E%7B-3%7D%7D%20)
Recall the exponent rule => ![\frac{x^{a}}{x^{b}} = x^{a - b}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx%5E%7Ba%7D%7D%7Bx%5E%7Bb%7D%7D%20%3D%20x%5E%7Ba%20-%20b%7D%20)
Applying the exponent rule, we would have:
![\frac{b^{-2 -(-3)}}{a}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bb%5E%7B-2%20-%28-3%29%7D%7D%7Ba%7D%20)
![= \frac{b^{-2 + 3}}{a}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7Bb%5E%7B-2%20%2B%203%7D%7D%7Ba%7D%20)
![= \frac{b^{1}}{a}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7Bb%5E%7B1%7D%7D%7Ba%7D%20)
![= \frac{b}{a}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7Bb%7D%7Ba%7D%20)
Thus, the equivalent expression of
= ![\frac{b}{a}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bb%7D%7Ba%7D%20)
Answer:
12s² + 11st - 2t²
Step-by-step explanation:
Each term in the second factor is multiplied by each term in the first factor, that is
- 3s(4s - t) + 2t(4s - t) ← distribute both parenthesis
= - 12s³ + 3st + 8st - 2t² ← collect like terms
= - 12s² + 11st - 2t²
Combine like terms.
5c = 45
Divide 5 on both sides.
c = 9
Hope this helps!
Answer:
the ratio is 5 to 1.
Step-by-step explanation: